Carbon fibres reinforced composites. Electrical impedance analysis: a gateway to smartness. Issue 4 (1st October 2020) - Margueres, Philippe; Olivier, Philippe; Mounkaila, Mahamadou; Sassi, Sonia; Camps, Thierry
ABSTRACT: For more than 7 years, our research work is focussed upon the electrical behavior of carbon fiber reinforced composites. Effectively carbon/polymeric matrix laminates can be considered as an electrically conductive network (i.e. carbon fibers) embedded in an insulating medium (i.e. the polymeric matrix). Consequently, from an electrical point of view laminated composites have been modelled owing to combinations of electrical resistances (i.e. fibers themselves and the contact points between the fibers) and capacitances (i.e. polymeric matrix). During their manufacturing, composite material such as thermoset matrix composites for instance, undergo various changes in their physical (including electrical and mechanical) properties and in their geometrical characteristics. In fact, in the case of manufacturing processes such as oven curing (vacuum bag), autoclave curing or heating plate press, beside the chemo-rheological changes, the laminated parts are the place of a compaction phenomenon inducing changes in fiber volume fraction and thicknesses. The idea developed in this paper is that since the carbon/polymeric matrix laminate can be considered as an electrical network, it can then be view and used as a sensor for following the material state during the manufacturing process enabling thus defects to be detected and this without any additional sensing material or device.